Inflammatory Bowel Diseases (IBDs) vs Irritable Bowel Syndrome (IBS): A comparative qualitative study on prevalent themes, emotions and Quality of Life (QoL) - Amelia RIZZO; Aurora MAUTONE; Francesco CHIRICO; Lukasz SZARPAK; Michal PRUC; Maria Grazia MAGGIO; Livio TARCHI; Kavita BATRA; Giuseppe FERRARI; Francesca BRUNO; Aldo SITIBONDO (Journal of Health and Social Sciences)
Introduction: Inflammatory bowel diseases (IBDs) (including Crohn’s disease, Ulcerative colitis) and Irritable Bowel Syndrome (IBS) are different debilitating conditions affecting the digestive system. Both diseases significantly impact patients’ lives, not only physically but also psychologically. Although some comparative literature exists, there is currently a lack of studies exploring qualitative differences in how pathology is experienced. In the present study, we explore the broad spectrum of psychological impacts caused by gastrointestinal disorders, including the experience of surgical interventions on the intestines, impact of the disease activity, severity of symptoms, and Quality of Life (QoL). Additionally, we examine how the diagnosis can be perceived as an emotional trauma for patients. Methods: A total of 366 participants was enrolled (aged between 18 and 65 years, Mage=37.06, SD=12.09), 82% of whom are female. Patients were divided into 4 subgroups and compared according to the gastrointestinal pathology: (1) Crohn’s disease (IBD); (2) Ulcerative colitis (IBD); (3) Irritable Bowel Syndrome (IBS); (4) Other condition / Subject awaiting diagnosis. From these participants, we obtained 87 descriptive texts (1668 words; 104 segments) about describing the pathological condition, emotional experiences, and experiential aspects related. The software MAXQDA Analytics Pro (v.22.7.0) was employed for the textual analysis of prevalent themes associated with each specific medical condition. Results: Statistically significant differences were found among the four intestinal condition groups in both perceived quality of life (χ² = 19.12, p = 0.0003) and diagnosis experience (χ² = 21.57, p = 0.043), worse for IBD group, suggesting that the perception of the impact of the intestinal condition varies depending on the diagnosis. The qualitative analyses highlighted emotional, psychological, and social aspects, including anxiety, depression, guilt, and social isolation, which significantly impacted the patients’ daily lives. Discussion: Previous research has primarily compared QoL across gastrointestinal conditions without delineating the distinct sources of suffering characterizing each disorder. The identification of significant differences in patient experiences and underlying themes supports a more precise and condition-specific personalization of therapeutic strategies and clinical management, emphasizing the necessity of adapting interventions to the unique clinical profiles of each patient population.